Examining the relationship between obstructive sleep apnoea and eating behaviours and attitudes: A systematic review. (1st February 2023) - Cassidy, Siobhán; Harvey, Leah; Smyth, Sinéad
Abstract: Background: Between 60 and 90% of adults with OSA are reported as overweight. The co-existence of obesity and OSA can greatly increase an individual's risk of type 2 diabetes, metabolic syndrome and cardiovascular disease. To better understand this relationship between OSA and weight, this review aimed to investigate if there is evidence of certain eating behaviours or eating attitudes that might be found in adults living with OSA. Methods: We searched four databases (MEDLINE, Embase, PsycInfo and Web of Science) on January 17th, 2022, to identify studies assessing the association between eating patterns and OSA in adults. Twenty-one studies met the inclusion criteria. A narrative synthesis was conducted on the included studies, following the vote-counting method. Results: There is preliminary evidence that the time of day when calories are consumed is associated with lower OSA severity. No other clear patterns of eating behaviours or attitudes were identified however this may be due to disparity within research studies and their reported results. Conclusion: Further research is needed to examine the relationship between eating times and OSA severity. We recommend standardising the approach to examining the eating patterns of those living with OSA and the relationship that this might have on OSA symptoms as well as looking at attitudes towards food in this population. This may prove helpful in providing a better understanding of the relationship between OSA and persons with overweight and help in future intervention development.